Sex-related disparities in outcomes of survival in biliary tract cancer patients - Nadiye Sever; Emil Yunusov; Nargiz Majidova; Erkam Kocaaslan; Pınar Erel; Yeşim Ağyol; Ali Kaan Güren; Abdussamet Çelebi; Selver Işık; İbrahim Vedat Bayoğlu; Osman Köstek; Murat Sarı (Journal of Cancer Research and Clinical Oncology)
Abstract Introduction Biliary tract cancer (BTC) is a rare and aggressive cancer with a poor prognosis. Despite treatment, overall survival is less than 12 months. It is a proven fact that women have better chemotherapy responses and survival than men in almost all cancer types. We believe that gender is one of the important factors affecting the prognosis of BTC. In this study, we aimed to investigate the effect of gender on prognosis in this type of cancer. Methods This study was designed as a single-centre retrospective analysis of patients with BTC. All patients, regardless of operability, were included in the study. Prognostic factors were analysed using univariate and multivariate analysis. Results A total of 100 patients (48% female) were included in the study. The median follow-up time was 72.2 months (95% CI 39.3–105.0), and the median OS was 9.5 months (95% CI 5.3–13.8) for all study patients. The 72-month survival rate was 13.4%. The observed survival rates at 10.4% for male patients and 15.7% for female patients demonstrate the importance of considering gender as a prognostic factor. A multivariate analysis indicated a significant association between female gender and longer overall survival, with an adjusted hazard ratio of 0.59 (95% CI 0.38–0.92, p = 0.02). Conclusion It is clear that female gender is associated with a better response to chemotherapy and longer survival in BTCs. These findings should be taken into account in treatment selection and prognosis predictions. Further research may help elucidate the mechanisms underlying these sex differences and help develop more effective treatments.